Eating the honey of words new and selected poems - Bly, Robert (New York, NY Perennial, 2000)
Robert Bly has had many roles in his illustrious career. Now, in Eating the Honey of Words, he presents the best poems he has written in the last three decades, including favorites from his earlier books such as Silence in the Snowy Fields, The Man in the Black Coat Turns, and Loving a Woman in Two Worlds. Joining these timeless classics are a number of poems from these past decades never published before, as well as a complete section of new poems from the last two years.
Early poems (1950-55) -- Silence in the snowy fields (1958-78) -- Light around the body (1957-70) -- Teeth mother naked at last (1970-72) -- The Point Reyes poems (1965-84) -- Loving a woman in two worlds (1973-81) -- This body is made of camphor and gopherwood (1973-80) -- The Man in the black coat turns (1980-84) -- Meditations on the insatiable soul (1990-94) -- Morning poems (1993-97) -- New poems (1997-98)
Keywords: American poetry -- 20th century